Status of membrane distillation for water and wastewater treatment-a review - Pangarkar, Bhausaheb L.; Sane, Mukund G.; Parjane, Saroj B.; Guddad, Mahendra (Desalination and Water Treatment, 2014)
Membrane distillation (MD) is a promising separation technique for water treatment. It is a nonisothermal process known since 1963. However, this technology still needs to be developed for its industrial implementation for different purposes. This paper presents a status review of MD based on the available published literatures and on preliminary analysis. The review covers the concept, membranes and modules design, configurations, performance parameters, fouling phenomena, the heat and mass transfer phenomena, applications, energy assessment, heat integration, and Memstill technology of MD process. Earlier study indicates that the permeate quality obtained by MD is stable and practically independent on the feed concentrations. The permeate flux is strongly affected by the feed temperature, feed flow rate, vacuum pressure in vacuum MD, and the boundary layer heat transfer coefficient. The permeate flux obtained in the literature of MD process is disagree by an order of enormity and hence better experimental work is needed. The less attention was found in the literature towards the removal of organic and inorganic toxic constituents from the groundwater by MD process.
Keywords: Fouling; Membrane configuration; Membrane design; Membrane distillation; wastewater